PARENTAL BONDING DAN KEMANDIRIAN PADA REMAJA - Ulpa, Eska Prawisudawati; Siti Tsabitah Suryakusuma; Mustamira Sofa Salsabila (Indonesian Journal of Social Science and Education (IJOSSE), 2025)
A The phenomenon of adolescents lacking independence has attracted the attention of many parties, particularly within the school and family environments. For instance, many teachers and parents report that junior high school students still rely on their parents for simple matters, such as preparing school supplies, arranging study schedules, and even choosing extracurricular activities. On the other hand, there are also adolescents who demonstrate a high level of independence because they are accustomed to making their own decisions at home. This research uses a quantitative method with purposive sampling as the sampling technique. The subjects involved in this study consist of 100 early adolescents from Bandar Lampung. The reliability of the independence scale was 0.781 and the parental bonding scale was 0.725. This is shown by the correlation coefficient value of R = 0.347 and R² = 0.120, with a significance level of p < .001.